Thermal Decomposition Kinetics of Dracaena Draco Agro Waste: An Investigation Employing Multicomponent Models and Gaussian Deconvolution - Hadou, Abdelwaheb; Belaadi, Ahmed; Alshahrani, Hassan; Boumaaza, Messaouda; Alshaikh, Ibrahim M. H.; Ghernaout, Djamel (Taylor & Francis, 2025)
This study examines the pyrolysis behavior, kinetic parameters, and thermodynamic features of Dracaena draco fibers (DdFs), an underutilized subtropical agro-waste from areas such as Algeria and the Canary Islands. With a low ash content (2.10%, reducing slagging issues compared to rice husks?~?15%), high volatile matter (77.29%, favoring bio-oil yields?>?50%), and elevated lignin (26.78%, enhancing energy density with HHV 19.95?MJ/kg), DdFs offer unique advantages over other biomasses that have been extensively studied, like rice husk or sugarcane bagasse. Using thermogravimetric analysis, samples werea pyrolyzed in a nitrogen environment at heating rates ranging from ambient to 800C at rates of 5-30 C/min. By better resolving early-stage drying effects, a novel four-parallel Gaussian kinetic model that incorporates pseudo-drying (PO-D) along with pseudo-hemicellulose (PO-H), pseudo-cellulose (PO-C), and pseudo-lignin (PO-L) accurately describes decomposition with R2?>?0.99, RMSE?<?0.05, and ?2?<?0.01. This model outperforms conventional three-component models. The mean apparent activation energies of 146.93?kJ/mol (PO-H), 127.76?kJ/mol (PO-C), and 173.94?kJ/mol (PO-L) obtained using model-free isoconversional methods (Starink, Kissinger-Akahira-Sunose, and Ozawa-Flynn-Wall) show better thermal stability for lignin charring than agave (PO-L?~?106?kJ/mol).